2021
DOI: 10.1093/poq/nfab002
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Questions in Surveys

Abstract: In research on sensitive questions in surveys, the item count technique (ICT) has gained increased attention in recent years as a means of counteracting the problem of misreporting, that is, the under- and over-reporting of socially undesirable and socially desirable behaviors or attitudes. The performance of ICT compared with conventional direct questioning (DQ) has been investigated in numerous experimental studies, yielding mixed evidence. This calls for a systematic review. For this purpose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Because both samples are presented with the same control list and are randomly assigned, any difference between the average response of the two groups is due to the additional sensitive item. The technique has been most widely used in political science research on voting and research on racism and attitudes to immigration (Krumpal, 2013;Ehler et al, 2021).…”
Section: List Experimentsmentioning
confidence: 99%
“…Because both samples are presented with the same control list and are randomly assigned, any difference between the average response of the two groups is due to the additional sensitive item. The technique has been most widely used in political science research on voting and research on racism and attitudes to immigration (Krumpal, 2013;Ehler et al, 2021).…”
Section: List Experimentsmentioning
confidence: 99%
“…Equation (10) includes the two variances V ( p1 ) and V ( p2 ), which are calculated applying Eq. ( 4), and the covariance term C( p1 , p2 ), addressing the levels of dependence of z and u in s 1 , and x and w in s 2 , respectively (for the details see Appendix 1).…”
Section: The Item Count Techniquementioning
confidence: 99%
“…Moreover, the interviewees do never have to supply the answer on the sensitive question directly. Various experiments examined the effectiveness of the method (cf., for instance, Droitcour et al [9], Tsuchiya et al [27], Coutts and Jann [8], Comsa and Postelnicu [7], Kiewiet de Jonge and Nickerson [16], Wolter and Laier [28], Blair et al [2], and in particular the meta-analysis by Ehler et al [10]). Exciting application examples can be found, for instance, in Comsa and Postelnicu [7], Malesky et al [17], Frye et al [11], Gibson et al [12], Rinken et al [21], or Wolter et al [29].…”
Section: Introductionmentioning
confidence: 99%
“…Although researchers do have statements or procedures to ensure the confidentiality of respondents, several studies have shown that respondents always seem not to put their trust in such assurances. As a result, in many cases, when asked directly about sensitive conduct or matters, they refuse to provide information [30], or information is distorted [31].…”
Section: Instrumentmentioning
confidence: 99%